The Implementation of Group Guidance Services to Improve the Behavior of Students' Courtesy - Fathoni, Yanuar Ikhsan; Fithriyana, Arina (Konseling Edukasi : Journal of Guidance and Counseling, 2024)
Politeness behavior is one of the important aspects in the development of students' character that should be considered in the education process. However, in reality, many students still exhibit a lack of polite behavior both within and outside of school. This research aims to determine the implementation of group guidance to improve the polite behavior of students at MA Mazro’atul Huda Wonorenggo Demak.This research employs a qualitative approach with a field research design. The subjects of this study are students, guidance counsellors, and the school principal. Meanwhile, the data is collected through observation, interviews, and documentation. In analyzing the data, the researcher utilizes data reduction, display, and verification processes, which involve selecting relevant data, presenting it clearly, and drawing conclusions.The research findings indicate that the guidance counselor’s teacher has carried out the implementation of group guidance services to improve the etiquette behavior of students effectively. Supporting factors include student participation in group guidance services, support from the school principal, and collaboration between the guidance counselor’s teacher and other subject teachers. The inhibiting factors include initial lack of enthusiasm from students during the service provision and students' lack of self-confidence.  The impact after the implementation of group guidance related to etiquette behavior shows that this service is most effectively applied to students, as evidenced by improved attitudes compared to before receiving services from the guidance counsellor.Keywords: Group Guidance, Polite Behavior, MA Mazro'atul Huda.